Anti-tuberculosis Conjugates Based on Polysaccharides - Shomurotov Shavkat Abduganievich; Mamatmusaeva Nilufar Erkinovna; Sagdullaev Bakhodir Takhirovich; Turaev Abbaskhan Sabirkhanovich (Genius Journals, 2022)
The research on the synthesis of polymeric complexes of polygalacturonic acid with anti-TB preparations having antituberculosis activity was conducted. The structures were ascertained and studied the physicochemical properties of polymeric systems. Pharmacotoxicological studies have shown that polymeric complexes are less toxic than their low molecular analogues and Mycobacterium of tuberculosis show high sensitivity to the prepared preparations.
Keywords: polymeric complexes; tuberculosis; prolongation; ethambutol